Sodium Dodecyl Sulfate Adsorption onto Positively Charged Surfaces: Monolayer Formation With Opposing Headgroup Orientations - Song, Sang-Hun; Koelsch, Patrick; Weidner, Tobias; Wagner, Matthew S; Castner, David G (Langmuir, 2013)
The adsorption and structure of sodium dodecyl sulfate (SDS) layers onto positively charged films have been monitored in situ with vibrational sum-frequency-generation (SFG) spectroscopy and surface plasmon resonance (SPR) sensing. Substrates with different charge densities and polarities used in these studies include CaF2 at different pH values as well as allylamine and heptylamine films deposited onto CaF2 and Au substrates by radio frequency glow discharge deposition. The SDS films were adsorbed from aqueous solutions ranging in concentration from 0.067 to 20 mM. In general the SFG spectra exhibited well resolved CH and OH peaks. However, at SDS concentrations between 1 and 8 mM the SFG CH and OH intensities decreased close to background levels. Combined data sets from molecular conformation, orientation, and order sensitive SFG with mass sensitive SPR suggest that the observed changes in SFG intensities above 0.2 mM are related to structural arrangements in the SDS layer. A model is proposed where the SFG intensity minimum between 1 and 8 mM is associated with a monolayer containing two headgroup orientations, one pointing toward the substrate and one pointing toward the solution phase. The SFG peaks observed at concentrations below 0.2 mM are dominated by the presence of adsorbed contaminants such as fatty alcohols (e.g., dodecanol), which are more surface active than SDS. As SDS solution concentration is increased above 1 mM SDS molecules are incorporated in the surface layer, with dodecanol continuing to be present in the surface layer for solution concentrations up to at least the critical micelle concentration.